Bacteriological study of pyodermas in a tertiary care dermatological center - Suresh K Malhotra; Sita Malhotra; Gurjit S Dhaliwal; Alpna Thakur (Wolters Kluwer Medknow Publications, 2012)
Background: Bacterial skin infection especially Pyoderma, commonly caused by Staphylococcus aureus and group A Streptococci, is quite common in Indian dermatology clinics. Despite a number of new antibiotics, the incidence of bacterial resistance is rising. Aim: To find out causative organisms and their latest antibiotic susceptibility patterns in pyodermas. Materials and Methods: All in-patients admitted in the Dermatology wards in Government Medical College, Amritsar were screened over 18 months and those with erosive skin lesions and/or purulent discharge were included in the study and swabs were sent for culture and sensitivity. Results: Majority 49/61 cases (80.33%) comprised of secondary pyodermas while primary pyodermas constituted only 12/61 cases (19.67%). Single organism was isolated in 49 cases (80.33%). More than one type of organism was isolated in 3 cases (4.92%) while none could be isolated from 9 (14.75%) cases. Staphylococcus aureus spp. was the commonest organism isolated in 36 (59.01%) cases and out of these, coagulase positive strains were found to be highly susceptible to amikacin (21cases-100%). Coagulase negative strains were sensitive to amikacin (7 cases-77.7%) and gentamycin (6 cases-66.6%) respectively. Conclusion: This study gives an indication of the present pattern of bacteriological profile of pyodermas in a tertiary care hospital in north-west India. In-vitro testing is essential as knowledge of the causative organisms and resistance patterns can help us select appropriate antibiotics without wasting time in using resistant drugs.